Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.3109/00365529609004879
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Diastolic Function in Liver Cirrhosis

Abstract: The impaired left ventricular relaxation in the presence of high stroke volume suggests a myocardial involvement in LC. The pseudo normalization of the E/A ratio and DT in patients with tense ascites could reflect loading conditions masking the relaxation abnormality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
105
0
6

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(119 citation statements)
references
References 18 publications
8
105
0
6
Order By: Relevance
“…Actually, most previous studies have investigated patients with mixed etiologies of liver disease [13,14] introducing a bias in the interpretation of results according to the known potential interference of various exogenous factors and pathologic conditions on cardiovascular variables. Nevertheless diastolic dysfunction has been reported even in patients with idiopathic (non cirrhotic) portal hypertension [16], pointing to the role of hemodynamic derangement characterizing advanced cirrhosis [24,29] as the leading factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, most previous studies have investigated patients with mixed etiologies of liver disease [13,14] introducing a bias in the interpretation of results according to the known potential interference of various exogenous factors and pathologic conditions on cardiovascular variables. Nevertheless diastolic dysfunction has been reported even in patients with idiopathic (non cirrhotic) portal hypertension [16], pointing to the role of hemodynamic derangement characterizing advanced cirrhosis [24,29] as the leading factor.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperdinamic circulation [3], QTc prolongation [4,5], beta-receptors desensitization [6,7], reduced systolic competence under strains [8][9][10][11] and diastolic dysfunction [12][13][14][15][16][17] are the key features of cirrhotic cardiomyopathy. Diastolic dysfunction, characterized by an altered pattern of transmitral flow due to impaired diastolic relaxation of left ventricle, can be easily assessed by echocardiography and accordingly can be considered as a marker of this condition.…”
Section: Introductionmentioning
confidence: 99%
“…Removal of the ascitic fluid by rapid total paracentesis reduces the A wave velocity and increases the E/A ratio to values similar to those of cirrhotic patients without ascites but still abnormal as compared with healthy controls. Finucci et al [11] reported increased stroke volume, left ventricular end-diastolic volume, left atrial volume, peak A velocity, deceleration time of E wave, and decreased E/A ratio (1.02 vs. 1.22) in 42 Child-Pugh class B and C cirrhotic patients, half of whom with alcoholic etiology. The prolonged deceleration time was unaffected by the presence of ascites.…”
Section: Diastolic Dysfunctionmentioning
confidence: 99%
“…Over the last 2 decades, there is accumulating evidence to suggest that the presence of cirrhosis per se is associated with significant cardiovascular abnormalities, irrespective of the cause of cirrhosis. These include resting increased cardiac output; decreased systemic vascular resistance [1]; reduced myocardial contractility or systolic incompetence, especially under conditions of stress, whether physiological [5], physical [6,7], or pharmacological [8]; increased thickness of the left ventricle [9][10][11], associated with diastolic dysfunction; and electrophysiological abnormalities [12][13][14]. This constellation of abnormalities has been termed cirrhotic cardiomyopathy [15].…”
Section: Introductionmentioning
confidence: 99%
“…When both organs are performing well, they are seemingly oblivious of one another, but when one fails or is dysfunctional, the other is likely to suffer. Cirrhosis and portal hypertension dilate the vasculature, 10 cause the heart to beat harder and faster, 11 raise the pressure in the pulmonary vascular tree, 12 interfere with both systolic 13,14 and diastolic function, 15 and even meddle with ventricular depolarization by decreasing conductance of potassium channels to prolong the Q-T interval. 16 By way of reciprocation, when there is cardiac misbehavior the liver feels the brunt, irrespective of whether it is the left heart or the right heart that is at fault, or both.…”
mentioning
confidence: 99%